2017
DOI: 10.1088/1741-2552/aa620a
|View full text |Cite
|
Sign up to set email alerts
|

GLIMPSE: Google Glass interface for sensory feedback in myoelectric hand prostheses

Abstract: The present study demonstrates a novel self-contained, ready-to-deploy, wearable feedback interface. The interface was successfully tested and was proven to be feasible and functionally beneficial. The GLIMPSE can be used as a practical solution but also as a general and flexible instrument to investigate closed-loop prosthesis control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…Future research should investigate the interaction between task learning and feedback and explore how each of the feedback variables (e.g., ‘Touch’ , ‘Force’ , ‘DoF-switch’ ) contributes to the overall task performance. The subjective relevance of different feedback variables that were delivered simultaneously during prosthesis grasping was investigated in a recent study [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should investigate the interaction between task learning and feedback and explore how each of the feedback variables (e.g., ‘Touch’ , ‘Force’ , ‘DoF-switch’ ) contributes to the overall task performance. The subjective relevance of different feedback variables that were delivered simultaneously during prosthesis grasping was investigated in a recent study [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this and require that the subjects control the grasping force, we equipped each pin with a switch and a small LED. If the subjects produced an excessive force during grasping, the pin opened too much, closing the switch and activating the LED (see Figure 2D2) [ 53 ]. An activated LED simulated the breaking of the clothespin and forced the subjects to repeat the grasp.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies ( e.g . 14 , 20 , 21 ) have shown that sensory feedback improves performance, others ( c.f . 14 ) have concluded that sensory feedback had no effect on performance.…”
Section: Introductionmentioning
confidence: 99%
“…Vibro-tactile 13 , mechano-tactile 14 , electrotactile [15][16][17] , skin stretch 18 , and auditory 19 are just some of the techniques that have been developed and used to provide prosthesis users with feedback. Although some studies (e.g., 14,20,21 ) have shown that sensory feedback improves performance, others (c.f., 14 ) have concluded that sensory feedback had no effect on performance. This lack of consensus arises, at least in part, because of an unclear understanding of how the incorporation of feedback relates to performance.…”
Section: Introductionmentioning
confidence: 99%
“…Humans use visual feedback along with other sensory and proprioceptive information to develop their internal model, however constant visual attention and the high level of concentration it requires may lead powered prosthesis users to reject their devices 28 . Conveniently, augmented feedback can be used to convey artificial proprioceptive and exteroceptive information 21,29 , which may help to develop strong internal models. Researchers have used audio augmented feedback in both robotic teleoperation 30,31 and Brain Computer Interfaces (BCI) 32 and have concluded that audio augmented feedback improves performance.…”
Section: Introductionmentioning
confidence: 99%